Teen pregnancy involvement among African, Caribbean and Black adolescent boys and girls: A scoping review - Elizabeth Saewyc; Emmanuela Ojukwu; Eunice Bawafaa; Sara Afsah; Shivangi Singh; Harsimran Grewal; Emily McKay (BMJ Open, 2024)
Objectives This study aims to investigate the incidence, associated factors and interventions to address teen pregnancy involvement (TPI) among African, Caribbean and Black (ACB) adolescents in North America.Design We conducted a scoping review of the literature, guided by the social-ecological model.Data sources Studies were retrieved from databases such as Ovid Medline, Ovid Embase, CINAHL, CAB Direct and Google Scholar and imported into COVIDENCE for screening.Eligibility criteria The Joanna Briggs Institute scoping reviews protocol guided the establishment of eligibility criteria. Included studies focused on rates, associated factors and interventions related to TPI among ACB boys and girls aged 10–19 in North America. The publication time frame was restricted to 2010–2023, encompassing both peer-reviewed and non-peer-reviewed studies with diverse settings.Data extraction and synthesis Data were extracted from 32 articles using a form developed by the principal author, focusing on variables aligned with the research question.Results The scoping review revealed a dearth of knowledge in Canadian and other North American literature on TPI in ACB adolescents. Despite an overall decline in teen pregnancy rates, disparities persist, with interventions such as postpartum prescription of long-acting birth control and teen mentorship programmes proving effective.Conclusion The findings highlight the need for increased awareness, research and recognition of male involvement in adolescent pregnancies. Addressing gaps in housing, employment, healthcare, sexual health education and health systems policies for marginalised populations is crucial to mitigating TPI among ACB adolescents.Impact The review underscores the urgent need for more knowledge from other North American countries, particularly those with growing ACB migrant populations.